Economic evaluation of public health interventions - Moran, Patrick (Trinity College (Dublin, Ireland). School of Medicine. Centre of Health Policy and Management, 2016)
This thesis examines the clinical and cost effectiveness of three separate public health interventions that are on the health policy agenda in Ireland and provides information to inform resource allocation at a national level. It also explores the possibility of expanding the role of economic analysis within the public health sector, with the aim of generating a more informed discussion about resource allocation priorities and gradually guiding policymaking towards the long term goal of achieving the mix of interventions that optimises health outcomes within the population. The Public Health (Availability of Defibrillators) Bill 2013 proposes a national public access defibrillation scheme that would require a range of designated places frequented by the public to provide defibrillators and train staff in their use.
Keywords: Health Policy & Management, Ph.D.; Ph.D. Trinity College Dublin 2016.